Redescription of Paraclimenes gorgonicola (Bruce, 1969) (Crustacea: Decapoda: Palaemonidae) and establishing P. franklini (Bruce, 1990) as its junior synonym - Park, Jin-Ho; Fransen, Charles H.j.m. (Zootaxa, 2021)
The octocoral associated species Paraclimenes gorgonicola is a deep-sea palaemonid shrimp briefly described in Bruce (1969) without illustrations. Paraclimenes franklini, the type species of the genus Paraclimenes, has been considered as a valid species and distinguished from P. gorgonicola by the presence of articulated postrostral teeth on the carapace. Paraclimenes gorgonicola is herein fully redescribed and illustrated on the basis of the type series which is deposited in Naturalis Biodiversity Center, Leiden, The Netherlands and recently collected specimens from shallow waters around Jejudo Island, Korea, and compared with P. franklini. It is demonstrated that both taxa are conspecific and thus P. franklini is considered to be a junior synonym of P. gorgonicola.